Public communication at research universities: Moving towards (de)centralised communication of science? - Entradas, M. (Public Understanding of Science, 2022)
This research note reports empirical observations on public communication of research institutes within universities, using data from an international quantitative study in eight countries (N = 2030). The note aims to contribute to discussions on the role of science communication at research universities. We observe growing science communication at the institute level, which indicates, at a first glance, a trend towards decentralised communication of science. We argue that these might be places where science communication and public engagement can thrive. Rather than claiming to be conclusive, our goal here is to stimulate discussion on the ongoing changes in the organisational science communication landscape, and the consequences it may have for practice.